2387. Selecting Clostridium difficile Infection (CDI) Outcome Measures Relevant to Public Health Concerns: Experience From a Ridinilazole (RDZ) Phase 2 Trial. (26th November 2018) - Vickers, Richard; Chowdhury, Sumita
Abstract: Background: CDC recognizes CDI as an immediate public health threat requiring urgent and aggressive action. Recurrent CDI (rCDI) occurs in up to 30% following initial therapy and 65% following a second recurrence. Perturbation by prior antibiotic use diminishes host colonization resistance allowing C. difficile to overgrow. Current CDI therapy with vancomycin (VAN) or metronidazole causes further collateral damage to the gut microbiota (GUT) priming patients for rCDI. Novel antibacterial agents are needed to tackle this life-threatening infection through (1) effectively treating initial CDI, (2) minimizing rCDI and (3) preventing collateral damage to GUT. A phase 2 trial with RDZ points to optimal selection of endpoints to capture these different benefits. Methods: Randomized double-blind phase 2 study to compare 10 days RDZ 200 mg BID to VAN 125 mg QID. The primary endpoint was SCR defined as cure with no recurrence to 30 days post end of treatment. Fecal samples from all patients were collected at baseline, days 5, 10, 25 and 40 and at recurrence and changes to the microbiome were assessed. Results: While clinical cure rates with RDZ and VAN were similar, RDZ-treated patients had a lower recurrence rate. As a result, in the primary efficacy analysis of 69 patients, 24 of 36 (66.7%) on RDZ vs. 14 of 33 (42.4%) on VAN had SCR (treatment difference 21.1%, 90% CI 3.1–39.1) establishing non-inferiority of RDZ ( P = 0.0004) and also showing statistical superiority at the prespecified 10% level. Improved SCR with RDZ was associated with limited GUT impact vs. substantial GUT perturbation seen on VAN; both therapies reduced C. difficile to below the limit of detection. Conclusion: SCR captures the impact of a therapy on both initial cure of CDI and rCDI. Applicable in randomized studies, it avoids methodological issues associated with recurrence as a separate endpoint. Moreover, by capturing impact on rCDI, it can assess superiority of novel therapies over existing agents with high cure rates. SCR should be a preferred measure of CDI treatment outcomes, and will be the primary endpoint in Phase 3 trials of RDZ. These trials will also evaluate GUT effects, so capturing three important determinants of public health impact: initial CDI, GUT and rCDI. Disclosures: R. Vickers, Summit Therapeutics: Employee, Salary and Stock options. S. Chowdhury, Summit Therapeutics Inc.: Employee and Shareholder, Salary and Shareholder.